PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PEMBIASAAN SALAT BERJEMAAH DI MTs MA'ARIF GEMAWANG TAHUN PELAJARAN 2021/2022 - Nuzul Fatimah; Husna Nashihin; Ana Sofiyatul Azizah (Al Ghazali, 2022)
This research is motivated by the lack of awareness of students, the lack of teachers who accompany students during the zuhur prayer in congregation, and there is no firm sanction. The aim is to determine the implementation of congregational prayer habituation, the resulting character education values, as well as the supporting and inhibiting factors. This type of research uses field research, with qualitative research methods and a phenomenological approach. Sources of data come from primary and secondary data. The procedure for collecting data is by interviewing, observing, and documenting. Data analysis through data reduction, data presentation, verification. And check the validity of the data using triangulation of data sources. The results of the research are divided into preparation and implementation activities. Preparatory activities include cleaning the prayer room, performing ablution, and the teacher preparing attendance. The implementation activities include the congregational noon prayer, students shake hands with each other, dhikr and pray together, and fill in attendance. The values ​​of character education produced include: religious, honest, disciplined, independent, democratic, friendly/communicative, peace-loving, fond of reading, environmental care, social care, and responsibility. Supporting factors in the form of students who have received material about prayer, support from parents, availability of ablution and prayer rooms, support activities at school. While the inhibiting factors come from the factors of teachers, students, and incomplete facilities. Keywords: congregational prayer, implementation, supporter, obstacle